Evolution and degradation pathways of landfill leachate DOC and detection of groundwater landfill-leachate contamination using compound-specific isotope analysis - Mohammadzadeh, Hossein (University of Ottawa (Canada), 2007)
Dissolved organic carbon (DOC) is a complex, yet major component of leachate and groundwater contamination derived from municipal solid waste burial. Here I use a new analytical technique for the analysis of 13C in specific compounds of DOC in leachate from the Trail Road Landfill (TRL) site, Ottawa, Ontario, in order to better characterize its biogeochemical and isotopic evolution during degradation; to determine methanogenesis pathways; and to identify characteristic tracers for recognizing potential of the leachate impact on the surrounding groundwater. This new operational system measures chromatographically-separated DOC compounds, and DOC compounds separated by DAX-8-resin, with a total inorganic/organic carbon analyzer (TCA) interfaced with a Thermo-Finnigan DeltaPlus continuous-flow isotope ratio mass spectrometer (CF-IRMS). At the TRL site, with capacity of 8.8 million cubic meters and a footprint of approximately 65 hectares, waste emplacement has been undertaken in four stages since the 1980s. Samples were collected in 2003 through 2005 from the leachate pumping station (LPS), which drains the areas of youngest waste, from monitoring well M32, situated at the base of the earliest stage and from leachate from waste up to 28 years old, and from several nested multilevel monitoring wells situated in the periphery of the landfill site. The following results were obtained based on isotope analysis of leachate, of landfill gases, of various leachate DOC components, and of contaminated groundwater. Leachate as a source of contamination has been characterized at different parts of the landfill as follows: (1) Elevated DOC and enriched 13CDOC values in old leachate from the older landfill (M32) (4770 mgl-1 and -21.6 ‰) in comparison with that of the younger leachate (LPS) (197 mgl-1 and -25.7 ‰) shows a fundamentally different biodegradation pathway and more advanced microbial processes in the degradation of dissolved organic mater (DOM) in the older part of the landfill. This resulted in the accumulation of simple fatty acids (acetate and propionate concentration of 1008 mgl-1 and 608 mgl-1, respectively) at the older part of the landfill with more enriched 13C values of acetic acid (-12.0 ‰) in comparison to that of young leachate at LPS (-16.9 ‰). (2) Deuterium excess provides a robust indicator of overall methane production, showing greater CH4 production in the younger parts of landfill than the older parts. The CO2 reduction pathway (alpha13C CO2-CH4=1.06) dominants at the younger landfill, however, acetate fermentation is the more favored CH4 production pathway at the older landfill. This can be confirmed with the less enriched 13CDIC (8.5 ‰) and a lower value for 2H excess (9.8 ‰) at M32. (3) The higher ratio of humic/fulvic acids (HA/FA) in young leachate compared to the old leachate (0.18 and 0.05 for LPS and M32, respectively) is due to high concentrations of FA (4482 mgl-1, 73% of the total DOC) and low concentrations of HA (21 mgl-1, 0.3% of the total DOC) in old M32 leachate. Less aromatic carbon in M32 (3% and 5% for POC and HA, respectively) in comparison with that of young leachate from the LPS (10% and 28% for POC and HA, respectively), estimated from 13C-NMR spectra, is perhaps due to degradation of HA and transforming of aromatic carbon to low molecule weight dissolved organic carbon (LMW-DOC), which is consistent with the high concentration of acetic acid (AA) in this older leachate. Although the elevated concentrations of leachate indicator parameters (like Cl and DOC) indicate that both shallow and deep aquifers have been contaminated at the TRL site, assessing the impact of landfill leachate on local groundwaters using geochemical parameters is often confounded by naturally elevated concentrations of these indicators. Here, environmental isotopes are used to provide a constraint in this assessment for leachate derived from the TRL site. The carbon geochemistry of different carbon pools (DIC, DOC, CH4, CH3COOH, humic substances (HS), particulate organic carbon (POC), particulate inorganic carbon (PIC)) and delta13C were used to recognize leachate impact on the surrounding groundwater. (Abstract shortened by UMI.)
Keywords: Geology.; Engineering, Sanitary and Municipal.; Environmental Sciences.; Geochemistry.